2016
DOI: 10.3892/ijo.2016.3358
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA expression profiling of mesothelioma and expression analysis of miR-1 and miR-214 in mesothelioma

Abstract: Malignant mesothelioma is a highly aggressive cancer with poor prognosis and refractory to currently available therapies. Most of the patients with advanced invasive nature are not amenable to surgical resection and/or available anticancer therapy, thus development of novel effective therapeutic regimes is needed. Aberrant expression of microRNAs (miRNAs) has been proposed to contribute to carcinogenesis and aggressiveness of mesothelioma. We analyzed miRNA expression in mesothelioma cell lines using TaqMan mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…However, information related to human studies is still largely lacking due to difficulty identifying LGR5 + cells in human intestine; this is probably due to the lack of appropriate antibodies and the low expression of LGR5. Alternate approaches, such as the use of SmartFlare RNA-based technology, are now being developed (54). To test the hypothesis that Lgr5 + stem cells are responsible for epithelial regeneration, several mouse models were developed to determine if an alternative stem cell population can replenish the intestinal epithelial under conditions in which Lgr5 + stem cells are ablated or damaged.…”
Section: Human Mini-intestines In the Study Of Intestinal Physiologymentioning
confidence: 99%
“…However, information related to human studies is still largely lacking due to difficulty identifying LGR5 + cells in human intestine; this is probably due to the lack of appropriate antibodies and the low expression of LGR5. Alternate approaches, such as the use of SmartFlare RNA-based technology, are now being developed (54). To test the hypothesis that Lgr5 + stem cells are responsible for epithelial regeneration, several mouse models were developed to determine if an alternative stem cell population can replenish the intestinal epithelial under conditions in which Lgr5 + stem cells are ablated or damaged.…”
Section: Human Mini-intestines In the Study Of Intestinal Physiologymentioning
confidence: 99%
“…Interestingly, miR‐99a was found at lower levels in MPM samples compared with normal pleura (Andersen et al ., ) and differentially expressed between epithelioid and sarcomatoid tumors (Pass et al ., ). Similarly, miR‐214 was shown to be downregulated in MPM samples compared with controls in two independent studies (Amatya et al ., ; Balatti et al ., ). In addition, we found that FGF signaling suppressed the expression of miR‐23a and miR‐223, both of which are altered in MPM and predicted to target components of the FGF axis (Birnie et al ., ; Cheng et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…S2). Two other studies in MM generating miR microarray profiles also suggest that miR‐18a is significantly upregulated in MM cell lines and MM tumor tissue compared to normal tissue (Amatya et al ., ; Ramirez‐Salazar et al ., ). Although none of these studies identified any key downstream targets of miR‐18a, they do support our idea that miR‐18a plays an important role in MM.…”
Section: Discussionmentioning
confidence: 99%